The SDG accelerator: Circular economy solutions through efficient sustainable consumption - Anupam Khajuria; Prabhat Verma; Atienza Vella; Daniela Zanini-Freitag; Hao Xin; Indu K. Murthy; Jatinder K. Arora; Kamani Sylva; Lakshmi Menon; Sushma Pardeshi; Ulrich Kral; Xiao Liu (Circular Economy)
The integration of sustainable consumption, education, and circular economy principles is essential for effective waste management and achieving the United Nations sustainable development goals (UN SDGs). This research approach, including applied project conclusions, examines the role of education in promoting sustainable consumption and circular economy practices, highlights key aspects of circular economy solutions and addresses the challenges of waste management in India, China, and the Philippines. This paper draws on sessions from the 18th and 19th International Conference on Waste Management and Technology, which focused on expanding waste management services and integrating quality education for sustainable practices. The findings underscore the importance of robust waste management policies, public awareness, and innovative recycling technologies to achieve sustainable consumption and production (SCP). Furthermore, the paper emphasizes the need for collaboration among policymakers, educational institutions, and industry stakeholders to foster a culture of sustainability and circularity. By leveraging education to drive systemic changes in consumption patterns and waste management, this study contributes to a deeper understanding of how these elements collectively support the achievement of the UN SDGs, particularly SDG 12 (responsible consumption and production) and SDG 4 (quality education).